2020
DOI: 10.1080/1943815x.2020.1779092
|View full text |Cite
|
Sign up to set email alerts
|

Land-use change and Biogeochemical controls of soil CO2, N2O and CH4 fluxes in Cameroonian forest landscapes

Abstract: Deforestation and land-use change are accelerating in the Congo Basin and elsewhere in the tropics affecting the soil-atmosphere exchange of greenhouse gases (GHG). There is a lack of data from Central Africa. We quantified fluxes of CO 2 , CH 4 , and N 2 O at the soilatmosphere interface in a secondary forest, a cocoa agroforest, and an unfertilized cropland. Soil respiration was highest in the secondary forest (15.37 ± 3.42 Mg C ha −1 y −1), intermediate in the cacao agroforest (12.26 ± 2.91 Mg C ha −1 y −1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 73 publications
4
5
0
Order By: Relevance
“…The latter study has higher clay contents compared to our study sites, which explains their correspondingly lower CH 4 uptake rate (Veldkamp et al., 2013). Compared to measurements conducted in sub‐Saharan Africa, our lowland forests had comparable soil CH 4 uptake rates as those reported for a tropical lowland forest in Cameroon (−41.1 to 51.6 μg C m −2 h −1 ; Tchiofo Lontsi et al., 2019; Verchot et al., 2020), and for tropical montane forests in Kenya (−35.4 to −66.2 μg C m −2 h −1 ; Wanyama et al., 2019) and in Tanzania (−31.0 to −44.6 μg C m −2 h −1 ; Gütlein et al., 2018). Conversely, our mean soil CH 4 uptake was lower than reported for tropical montane forests in Kenya (−56.4 μg C m −2 h −1 ; Werner et al., 2007), which had a sandy soil texture compared to our sites.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The latter study has higher clay contents compared to our study sites, which explains their correspondingly lower CH 4 uptake rate (Veldkamp et al., 2013). Compared to measurements conducted in sub‐Saharan Africa, our lowland forests had comparable soil CH 4 uptake rates as those reported for a tropical lowland forest in Cameroon (−41.1 to 51.6 μg C m −2 h −1 ; Tchiofo Lontsi et al., 2019; Verchot et al., 2020), and for tropical montane forests in Kenya (−35.4 to −66.2 μg C m −2 h −1 ; Wanyama et al., 2019) and in Tanzania (−31.0 to −44.6 μg C m −2 h −1 ; Gütlein et al., 2018). Conversely, our mean soil CH 4 uptake was lower than reported for tropical montane forests in Kenya (−56.4 μg C m −2 h −1 ; Werner et al., 2007), which had a sandy soil texture compared to our sites.…”
Section: Discussionsupporting
confidence: 75%
“…Forest conversion to CAF in our study sites generally lacked heavy land preparation activities and soil physical disturbance, and all our cacao sites were unfertilized, which may have resulted in the similar soil texture, bulk density and moisture contents between the two land uses at each site (Tables and ), and consequently, comparable CH 4 uptake. Our CAF sites had comparable soil CH 4 uptake rates (Table 2) as those reported for CAF in Cameroon (−41.2 μg C m −2 h −1 ; Verchot et al., 2020). The higher soil CH 4 uptake in our CAF sites compared to the jungle rubber agroforestry on highly weathered Acrisol soils in Indonesia (−20.8 to −26.9 μg C m −2 h −1 ; Hassler et al., 2015) may be the result of the higher soil NO 3 − contents in our CAF sites, which may have simulated CH 4 consumption and/or reduced CH 4 production in the soil (Matson et al., 2017; Veldkamp et al., 2013).…”
Section: Discussionsupporting
confidence: 75%
“…Thailand (Hashimoto et al, 2004) and Hawaii (Townsend et al, 1995); within range to those from the Democratic Republic of Congo (Baumgartner et al, 2020), Panama (Koehler et al, 2009a;Pendall et al, 2010), Brazil (Sousa Neto 335 et al, 2011), and Cameroon (Verchot et al, 2020); and higher than those reported from Kenya (Wanyama et al, 2019), andIndonesia (van Straaten et al, 2011). The differences in soil CO2 fluxes between the control plots in this study and studies done in other tropical forest sites may be due to differences in soil environmental characteristics e.g.…”
Section: Effect Of N and P Addition And Soil Environmental Controls Omentioning
confidence: 91%
“…Two key findings suggest that in LUC in tropical regions decreases soil respiration and the strength of CH 4 soil storage. Verchot et al (2020) observed that in the absence of fertilizer use, N 2 O emissions decreased with LUC. They also found that soil water content, instead of temperature, was the dominant driver of variability; average fluxes in the wet season were more pronounced than in the dry season.…”
Section: Verchot Et Al (2020) Land-use Change and Biogeochemical Controls Of Soil Co2 N2o And Ch4 Fluxes In Cameroonian Forest Landscapesmentioning
confidence: 98%
“…This Special Issue contains a selection of contributions to the symposium. It consists of this overview and seven topical papers as illustrative examples of the scientific results presented at the symposium (Wilson and Scholes 2020;O'neill et al 2020;Godwin and Ferenchiak 2020;Howarth 2020;Laban et al 2020;Verchot et al 2020;Zou and Osborne 2020). In the following section, we give an impression of the seven contributions.…”
Section: Diversity and Complexitymentioning
confidence: 99%